Liposarcoma of the spermatic cord mimicking a left inguinal hernia: a case report and literature review - Li Fubiao; Tian Runhui; Yin Changjiu; Dai Xiaofan; Wang Hongliang; Xu Ning; Guo Kaimin (World Journal of Surgical Oncology, 2013)
Abstract Liposarcoma of the spermatic cord (LSC) is a rare condition characterized by a painless inguinal or scrotal mass. To our knowledge, only about 200 cases have been previously reported in the literature. These tumors are often mistaken for common scrotal swellings, such as hydroceles and hernias. We present a LSC case in which a definitive diagnosis was obtained upon histological examination. We also provide a literature review of other cases that have been reported.